INFLUENCE OF PRICE, PRODUCT DESIGN AND THE NEED TO FIND VARIETY AGAINST BRAND TRANSFER DECISION (CASE STUDY ON EX SUZUKI MOTORCYCLE USERS IN BANDUNG CITY) - Yayan Rumdiana (Jurnal Ekonomi, 2022)
This research aims to determine how prices, product design, variety seeking and brand switching in ex Suzuki motorcycle users in the city of Bandung.The formulation of the problem of this research is how the influence of price, product design, variety seeking to the brand switching both partially and simultaneously. The research method used is a multiple linear analysis method. This research is categorized as a quantitative descriptive method research, where the instrument is in the form of observations, interviews and questionnaires. The population of this research was ex Suzuki motorcycle users in the city of Bandung. Samples taken as many as 100 respondents, the analysis used in this study include the research instrument test, classic assumption test, simple and multiple correlation test, determination test, t test and f test.The result of this research is the price variable (X1) has a positive and significant effect on brand switching (Y). Product design variable (X2) has a positive and significant effect on brand switching (Y). Variable variety seeking (X3) have a positive but not significant effect on brand switching (Y). And price variable (X1), product design (X2), variety seeking (X3) simultaneously influence to brand switching (Y